2009
DOI: 10.3382/ps.2008-00082
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass characteristics of female turkeys as affected by feeding programs

Abstract: A trial was conducted to evaluate the effects of different feeding programs on growth performance and carcass characteristics of Nicholas Large White female turkeys. Three different feeding programs were considered for a 12-wk period: 1) 3 diets fed for 4 wk each (starter 24% CP, grower 20% CP, and finisher diet 16% CP), 2) 2 diets fed for 6 wk each (starter-grower 22% CP and grower-finisher diet 18% CP), and 3) no change of diet for 12 wk (starter-grower-finisher diet 20% CP). From 0 to 4 wk of age, birds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Other authors [48] found that linoleic acid is more likely to be accumulated in dark meat, whereas n-3 long-chain fatty acids tend to be deposited in the white meat of chickens. The fat content of white meat from turkey breast is only 1%, and it is significantly lower than in dark meat from thighs, which accumulates most dietary PUFAs [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Other authors [48] found that linoleic acid is more likely to be accumulated in dark meat, whereas n-3 long-chain fatty acids tend to be deposited in the white meat of chickens. The fat content of white meat from turkey breast is only 1%, and it is significantly lower than in dark meat from thighs, which accumulates most dietary PUFAs [49]. …”
Section: Discussionmentioning
confidence: 99%
“…The average fat content in turkeys is 15% of their weight [10]. Unfortunately, it is not a valuable consumer product despite its low price [11]. Currently, turkey fat is used as a component of poultry products.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of fast-growing turkeys focuses on high growth intensities and correspondingly high yields of the breast muscles. Laudadio et al (2009) stated that changes in breast development can produce transformation in the growth of other muscles. However, Marks (1990) reported that fast growing birds deposit more fat than the slow-growing ones.…”
Section: Introductionmentioning
confidence: 99%